Pelatihan Penyusunan Progam Pendidikan Literasi Keuangan Melalui Implementasi Bank Mini Sekolah di SMKN 3 Muaro Jambi - Arpizal; Rosmiati; Putra, Iwan; Sari, Nurmala; Sri Dwijayanti, Novia (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The phenomenon of a wasteful lifestyle is often experienced by teenagers who are still in school because the youth group is a potential target so, financial literacy skills are really needed so the students are able to manage their finances personally and make economic decisions with logical reasons. To achieve this, community service activities are carried out using Participatory Action Research (PAR) method. Based on the result from the activity, it was found that aout of a total from 103 participants, 16 (15%) participants had wll literate level, 48 (47%) participants had sufficient literate level, 39 (38%) participants had less literate and there is no participants had not literate level. Futhermore, the educational program design at Bank Mini Sekolah at SMKN 3 Muaro Jambi consist of: a savings service program (Magema), financial recording practices, and banking professional work pratices. Through the implementation of the program, not only to improve the financial literacy skills of students and school residents, practical learrning for students, it also instills a good attitude in financial management with a (culture of) fondness for saving.